Origin and destination inference of bus passengers: Isnabul case study - Fidanoğlu, Akif. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2014)
With the advance technology used in the public transportation systems it has become much easier to monitor the trips of the passengers. Most of the public transportation systems record the passengers when they start their trip with the help of Automated Data Collection (ADC) systems installed to the vehicles. By this way, transit agencies records the origins of the passengers’ trips. However, it is a bit challenging issue to detect the passengers’ destination especially for the bus passengers since there is no data recorded when the passengers exit from the system. This study explores the methods to infer the destination of the passengers and to generate the Origin-Destination (OD) matrices for the bus passengers by conducting a case study for a single bus route in İstanbul. To estimate the destinations of the passengers, several assumptions have been set in the previous studies. In this study, these assumptions were used to infer the alighting location of the bus passengers with further assumptions. New methods are established to infer the destination location of the trips which couldn’t be estimated with the present methods. The results are compared with the outputs of the surveys conducted on the studied route.
Keywords: Transportation -- İstanbul.; Automatic data collection systems -- Standards.